Follow‐up of the re‐evaluation of polyglycerol polyricinoleate (E 476) as a food additive. (4th May 2022) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Gundert‐Remy, Ursula; Gürtler, Rainer; Husøy, Trine; Manco, Melania; Mennes, Wim; et al.
Abstract: Polyglycerol polyricinoleate (PGPR, E 476) was re‐evaluated in 2017 by the former EFSA Panel on Food Additives and Nutrient sources added to Food (ANS). As a follow‐up to this assessment, in this opinion, the Panel on Food Additives and Flavouring (FAF) addresses the data gaps identified to support an amendment of the EU specifications for E 476. Additionally, this opinion deals with the assessment of the proposed extension of use for E 476 in edible ices and a revision of the maximum permitted level in emulsified sauces. The Panel concluded that the proposed extension of use, if authorised, would not give rise to a safety concern. Additionally, the Panel performed a risk assessment of undesirable impurities potentially present in E 476. The Panel concluded that the maximum limits in the EU specifications for the four toxic elements (arsenic, lead, mercury, cadmium) should be lowered based on actual levels in the commercial food additive E 476. The Panel also concluded that maximum limits for glycidyl esters and 3‐monochloropropanediol should be included in the EU specifications for E 476. Alternatively, the Panel recommends an amendment of the definition of E 476 to include a requirement that the fats and oils used in the manufacturing of E 476 comply with the respective EU legislation regarding suitability for human consumption. Further, the Panel recommends a modification of the definition of E 476 indicating that polyglycerol used for the manufacturing of E 476 should be produced from glycerol meeting the specifications for E 422 (Commission Regulation (EU) No 231/2012). In this case, respective specification limits for epichlorohydrin, acrolein and butanetriol would not be needed for E 476. Finally, the Panel concluded that the proposed method based on the determination of ricinoleic acid is suitable for the determination of E 476 content in food.